Feasibility analysis of Paya Lombang village for zakat community development program / Fadhilatul Munawwaroh, Laily Dwi Arsyianti and Mohammad Iqbal Irfany - Munawwaroh, Fadhilatul; Arsyianti, Laily Dwi; Irfany, Mohammad Iqbal (Universiti Teknologi MARA, 2021)
Poverty is still a problem for developing countries like Indonesia. The majority of poor people in Indonesia live in rural areas. BAZNAS, as an institution that collects and distributes zakat, has a Zakat Community Development (ZCD) program that is a mustahik community empowerment program in rural areas. This research aims to analyze the feasibility of Paya Lombang village in receiving zakat fund assistance through ZCD program and to examine priority dimensions contributing to the highest and the lowest values. This research is conducted by survey method through interview and focus group discussion by using questionnaires. The Multi-Stage Weight Index is used to analyze collected data. The result shows that, with a score of 0.59, Paya Lombang village is feasible enough to be considered as a rural area to be funded by zakat funds.